2023
DOI: 10.1155/2023/1939606
|View full text |Cite
|
Sign up to set email alerts
|

Denoising Method of Pipeline Leakage Signal Based on VMD and Hilbert Transform

Abstract: In order to solve the problem of low localization accuracy of water supply pipeline leakage detection using acoustic emission signals, a noise reduction algorithm based on variational mode decomposition (VMD) and Hilbert transform is proposed in this paper. Firstly, the leakage signal is decomposed into several intrinsic mode functions (IMF) using VMD, and the number of decomposition layers is determined, and the IMF component is transformed by Hilbert to get the marginal spectrum, and the noise are preliminar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Under laboratory conditions, however, it can be difficult to achieve the conditions of cracks, and there may be security risks. By consulting the relevant literature, many scholars have simulated leakage in the form of holes, such as in [12]. Therefore, in this experiment, the leakage point was simulated in the form of holes, and the diameter of the leak hole was 4 mm, as shown in figure 6(d).…”
Section: Experimental Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Under laboratory conditions, however, it can be difficult to achieve the conditions of cracks, and there may be security risks. By consulting the relevant literature, many scholars have simulated leakage in the form of holes, such as in [12]. Therefore, in this experiment, the leakage point was simulated in the form of holes, and the diameter of the leak hole was 4 mm, as shown in figure 6(d).…”
Section: Experimental Environmentmentioning
confidence: 99%
“…Jiang et al proposed a noise reduction algorithm based on variational mode decomposition (VMD) and Hilbert transform. Their results showed that the proposed algorithm effectively removed the noise in the leakage signal and improved the accuracy of the leakage location [12]. VMD, unlike EMD's cyclical sifting and stripping, is based on robust mathematical derivation, separating each component of the signal by iteratively searching for the optimal solution of a constrained variational model [13].…”
Section: Introductionmentioning
confidence: 99%